Living Hadîth Wakaf Menurut Ulama Tradisional dan Modern di Gresik - Al Hadi, Abu Azam (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
This article focuses on the meanings of hadîth on waqf according to traditionalist and modern âulama in Gresik, East Java. The signification of hadîth related to religious benefaction (waqf) certainly has various aspects in terms of the social and cultural contexts of the Prophetic traditions. Hadîth on waqf has been subject of different meanings reconstruction among Muslim jurists in contemporary context. According to tradisionalist âulama, waqf can be meant as sadaqah jâriyah. They maintain that waqf is turning over properties which have the value of benefit to administrators of waqf who are responsible to maintain the original form of properties. Meanwhile, modern âulama argue that waqf is turning over the âexistingâ property either eternally or temporally to be used directly and its benefit can be taken continously for the sake of common good or public interest. Waqf is sadaqah jâriyah, the reward of which flows continously. The meaning of âexistingâ is that the age of submitted property is determined by its economic value, or as it is written in the statement of waqf. Different meanings of waqf according to traditionalist and modern âulama are influenced by their educational backgrounds.